A safety evaluation of canagliflozin: a first-in-class treatment for type 2 diabetes. (November 2014) - Boyle, Luke D; Wilding, John PH
<x xml:space="preserve">Abstract</x> Introduction: Numerous treatments are available for type 2 diabetes mellitus (T2DM), which can improve insulin sensitivity or stimulate its secretion. These are usually unable to halt progression. Inhibition of glucose reabsorption from the renal filtrate was proposed as a novel therapeutic target. Sodium/glucose co-transporter 2 (SGLT2) inhibitors were developed accordingly, with <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=canagliflozin&logicalOpe1=OR&field2=articletitle&text2=canagliflozin&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">canagliflozin the first to launch in the US in 2013. Areas covered: The mechanism of action of canagliflozin, its pharmacokinetic data and its clinical applications and efficacy data from clinical studies of both subjects with T2DM controlled on diet and exercise, and those on glucose-lowering agents and insulin. The evaluation focuses primarily on the safety of canagliflozin in clinical trials conducted for initial registration due to limited post-marketing data, discusses safety in special populations, before comparing its safety with existing therapies. Expert opinion: Canagliflozin offers a novel therapeutic approach to T2DM; advantages include weight loss and blood pressure lowering with a low intrinsic risk of hypoglycaemia. The main adverse effects likely to be seen are a very small increase in risk of urinary tract infections and a modest risk of developing genital fungal infections. Studies suggest no increased risk of cardiovascular (CV) disease, but longer duration outcome studies are essential.